Macroeconomics in emerging markets - Montiel, Peter J. 1951- (Cambridge University Press, 2011)
"The macroeconomic experience of emerging and developing economies has tended to be quite different from that of industrial countries. Compared to industrial countries, emerging and developing economies have tended to be much more unstable, with more severe boom/bust cycles, episodes of high inflation, and a variety of financial crises. This textbook describes how the standard macroeconomic models that are used in industrial countries can be modified to help understand this experience, and how institutional and policy reforms in emerging and developing economies may affect their future macroeconomic performance. This second edition differs from the first in offering - extensive new material on themes such as fiscal institutions, inflation targeting, emergent market crises, and the Great Recession - numerous application boxes - end-of-chapter questions - references for each chapter - more diagrams, less taxonomy, and a more reader-friendly narrative - enhanced integration of all parts of the work"--Provided by publisher.